5x-3=3(2x-1)-x

Simple and best practice solution for 5x-3=3(2x-1)-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3=3(2x-1)-x equation:



5x-3=3(2x-1)-x
We move all terms to the left:
5x-3-(3(2x-1)-x)=0
We calculate terms in parentheses: -(3(2x-1)-x), so:
3(2x-1)-x
We add all the numbers together, and all the variables
-1x+3(2x-1)
We multiply parentheses
-1x+6x-3
We add all the numbers together, and all the variables
5x-3
Back to the equation:
-(5x-3)
We get rid of parentheses
5x-5x+3-3=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| (4*a)+7=-36 | | x/12=4;x= | | -6(-1+4n)-1=-91 | | 5+2n+2=12 | | 120x+0.30=50x+0.40 | | 3(x+2=4(x+1) | | (x+7)^2-36=0 | | 48/2=z | | 5x-2x+1=3x+15x-2/4 | | 1v+3=17 | | 56-11x+4x=77 | | -1=5x-16 | | x^2+20x+28=0 | | 4*x+7=36 | | y-2=22 | | 3n-5=7n-21 | | X^2/(.25-2x)^2=2 | | 2/5+1/10=1/2(n+4) | | 2n-5=9n+37 | | T^2+28t+625T=0 | | -(x-1)(-2)=3 | | (x+10)^2-72=0 | | -3a+56+5(28)+85+180=0 | | (x/4)-(5/2)=(x/8) | | 12/1.12=3/e | | X+6=-1+2x | | 3/2x+1/4=13/4 | | 0.5x-3.5=0.2×-0.5 | | 5x=10^12 | | 5/8=25/c | | x-3=8(x-3) | | x+0.1=4.9 |

Equations solver categories